Hydrophobic Drug/Toxin Binding Sites in Voltage-Dependent K+ and Na+ Channels - Van Theemsche, Kenny M.; Van de Sande, Dieter V.; Snyders, Dirk J.; Labro, Alain J. (Frontiers in Pharmacology, 2020)
In the Nav channel family the lipophilic drugs/toxins binding sites and the presence of fenestrations in the channel pore wall are well defined and categorized. No such classification exists in the much larger Kv channel family, although certain lipophilic compounds seem to deviate from binding to well-known hydrophilic binding sites. By mapping different compound binding sites onto 3D structures of Kv channels, there appear to be three distinct lipid-exposed binding sites preserved in Kv channels: the front and back side of the pore domain, and S2-S3/S3-S4 clefts. One or a combination of these sites is most likely the orthologous equivalent of neurotoxin site 5 in Nav channels. This review describes the different lipophilic binding sites and location of pore wall fenestrations within the Kv channel family and compares it to the knowledge of Nav channels.